Teknik Logos Pada Debat Pertama Kampanye Calon Presiden dan Wakil Presiden Republik Indonesia Tahun 2019 - Nurdiyani, Nurdiyani; Herwandi (UIR PRESS, 2021)
Debate is an activity of arguing between two or more parties, either individually or in groups, in discussing and resolving problems. The method used is descriptive method. Data collection techniques in this study are: documentation techniques, listening techniques and note taking techniques. Data analysis techniques in this study are data techniques, data presentation, drawing conclusions. The results of research on logos techniques in the first debate of the presidential and vice presidential candidate campaigns of the Republic of Indonesia found 57 data items and 23 samples / samples, where each speaker received as much data, for Joko Widodo entimem there were 19 speech data, Maruf Amin There are 6 data, Prabowo Subianto has 19 data and Sandiaga Uno 13 data, from the four speakers Jokowi and Prabowo got the same number of speech data, namely 19 data, while for the example / sample, Joko Widod got 15 data, Maruf Amin had no data, Prabowo Subianto has 6 data and Sandiaga Uno 2 data, from the four speakers Jokowi is superior in providing examples than the four speakers, namely 15 speech data.